Observed Subsurface Marine Heatwaves Driven by Subsurface Eddies in the Western Tropical Pacific Ocean - Shihan Li; Shijian Hu; Xiangzhou Song (Geophysical Research Letters)
Abstract Marine heatwaves (MHWs) are extreme warm water events with high impact, but the drivers of subsurface MHWs, particularly the role of subsurface eddies in the occurrence of subsurface MHWs, are unclear yet. Previous studies suggest that surface warm water convergence due to wind forcing is the major driver of subsurface MHWs in the western tropical Pacific Ocean. However, here we find that quite a few of subsurface MHWs in the western tropical Pacific Ocean show significant co‐occurrence with subsurface anticyclonic eddies using in situ observations from buoys and Argo floats. These co‐occurring events are characterized by a lens‐shaped temperature structure with a subsurface warm core and encircled by an anomalous anticyclonic circulation pattern. Subsurface anticyclonic eddies, accompanied by subsurface oceanic convergence and downwelling, lead to strong downward heat transport and onset of subsurface MHWs. These findings indicate that the subsurface eddies are also an important driver of subsurface MHWs.